Effect of neuronal nitric oxide synthase serine-1412 phosphorylation on hypothalamic–pituitary–ovarian function and leptin response. Issue 6 (26th February 2020) - Guerra, Damian D; Bok, Rachael; Cari, Evelyn Llerena; Nicholas, Cari; Orlicky, David J; Johnson, Joshua; Hurt, K Joseph
Abstract: Hypothalamic neuronal nitric oxide synthase (nNOS) potentiates adult female fertility in rodents by stimulating gonadotropin releasing hormone (GnRH) secretion, which in turn promotes luteinizing hormone (LH) release and ovulation. The mechanism of hypothalamic nNOS activation is not clear but could be via nNOS serine1412 (S1412) phosphorylation, which increases nNOS activity and physiologic NO effects in other organ systems. In female rodents, hypothalamic nNOS S1412 phosphorylation reportedly increases during proestrus or upon acute leptin exposure during diestrus. To determine if nNOS S1412 regulates female reproduction in mice, we compared the reproductive anatomy, estrous cycle duration and phase proportion, and fecundity of wild-type and nNOS serine1412➔alanine (nNOS S1412A ) knock-in female mice. We also measured hypothalamic GnRH and serum LH, follicle stimulating hormone (FSH), estradiol, and progesterone in diestrus mice after intraperitoneal leptin injection. Organ weights and histology were not different by genotype. Ovarian primordial follicles, antral follicles, and corpora lutea were similar for wild-type and nNOS S1412A mice. Likewise, estrous cycle duration and phase length were not different, and fecundity was unremarkable. There were no differences among genotypes for LH, FSH, estradiol, or progesterone. In contrast to prior studies, our work suggests that nNOS S1412 phosphorylation is dispensable for normal hypothalamic–pituitary–ovarian function and regular estrous cycling. These findings have important implications for current models of fertility regulation by nNOS phosphorylation. Abstract : nNOS serine-1412-alanine knock-in mice demonstrate normal estrous cycles and hypothalamic–pituitary–ovarian (H–P–O) function.